Geochemistry and petrology of dioritic rocks from Aur Island, Mersing, Johor / Fatin ‘Izzani Hazad - Fatin ‘Izzani , Hazad (2015)
Smaller granitoid occurrences of Late Cretaceous magmatism can be identified in the Central and Eastern Belts of Peninsular Malaysia. Study area, Aur and its surrounding islands (Dayang and Lang), is located 65km east coast off Mersing, Johor are the most easterly exposed Eastern Belt granitoids. The dioritic rocks from the study area have been dated as Late Cretaceous age (~80±1Ma), and the lithology of these islands consists entirely of plutonic rocks, without any observation of volcanic or metamorphic rock. Aur diorite was classified using QAP modal percentages, and the rocks fall into diorite, quartz monzodiorite and granodiorite field. Aur composite pluton can be distinguished into two members; mafic-end member: diorite and quartz monzodiorite (SiO2: 54.6-59 wt.%) and the felsic-end member: granodiorite (SiO2: 61-65.7 wt.%). The mafic-end members: diorite and quartz monzodiorite show the typical ophitic and sub-ophitic texture often found in mafic rock, with their major mafic phase are made of clinopyroxene and orthopyroxene, with minor biotite and hornblende. The felsic-end member: granodiorite shows a markedly different observation. Granodiorite has the typical hypidiomorphic granular texture, with hornblende and biotite as its major mafic phase. The contact between these two different members could not be distinguished clearly in the field but the rocks are gradational from a more mafic composition at the northern part of Aur Island to a more felsic composition at the southern and central part of the island. Aur pluton displays mafic and felsic magma interaction with the presence of rounded to ellipsoidal MME heterogeneously distributed throughout the pluton. Magma mixing texture; anti-rapakivi can only be observed in granodiorite, suggesting that there may have been an interaction between these two magmas at one point during magmatic evolution. Generally, the pluton is I-type, metaluminous with the mafic-end member showing high-K calc-alkaline trend while the felsic-end member shows shoshonitic trend. Both members show distinct geochemical differences on Harker diagram and the chondrite v normalized REE patterns are fractionated [(La/Yb)N=6.52-11.92] with weak negative Eu anomalies (Eu/Eu*=0.602-1.008). Both members show variable depletion at Rb, P, Zr, Sm and Eu, with a pronounced negative Nb and Ti anomaly. LIL modelling show that the mafic-members magmatic evolution are controlled by clinopyroxene, hornblende and plagioclase; and the felsic-end magmatic evolution are controlled by plagioclase, K-feldspar and biotite. A multi sources and different origins for both end members can be seen from geochemical and petrographic evidences, suggesting they were probably made up of individual batches of melt. However, continuous trend seen for both members on Rb/Sr vs SiO2, Sr vs CaO and REE patterns suggests that a connection exist between all of the rocks at some stage of their magmatic evolution. Geochemical plots, petrographic evidence and presence of MME rule out pure crustal derived magma genesis and suggest mixed-origin of magma generations.